Comparative analyses of eight primer sets commonly used to target the bacterial 16S rRNA gene for marine metabarcoding-based studies - Lee, Hyeon Been; Jeong, Dong Hyuk; Cho, Byung Cheol; Park, Jong Soo (Frontiers in Marine Science, 2023)
Next-generation sequencing (NGS), especially metabarcoding, is commonly used to study the diversity and distribution of microbes in diverse ecosystems. The choice of primer set is critical, given the drawbacks of short amplicons and amplicon sequencing bias inherent to metabarcoding. However, comparative analyses of primer sets have rarely been conducted using field samples. In this study, we compared eight commonly used primer sets, all targeting hypervariable regions in the bacterial 16S rRNA gene: 27F/338R (V1–V2), V2f/V3r (V2–V3), PRK341F/PRK806R (V3–V4), 341F/785R (V3–V4), 515F/806RB (V4), 515F/806R (V4), 515F-Y/926R (V4–V5), and B969F/BA1406R (V6–V8). We conducted NGS in triplicate, with >0.8 billion bases in total using coastal seawater samples. The representation of bacterial community composition varied significantly across the eight primer sets, despite being from the same sample. The 27F/338R primer set showed the highest number of operational taxonomic units (OTUs) and read counts, and accounted for 68% of all the order-level taxa found. Remarkably, a novel complementary combination of two primer sets, 27F/338R and 515F/806RB, covered 89% of all the orders that were present. Compared to other primer sets, this combination detected more OTUs of the orders Pelagibacterales and Rhodobacterales, which are ubiquitous in the oceans. As such, use of this combination in future studies may help to reduce diversity bias in ocean-derived samples, in particular temperate coastal samples.